International experience in honoring science, technology and innovation products - Nguyen, Hong Anh (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2022)
Nowadays, countries, territories and organizations around the world have many forms to honor science, technology and innovation products with different selection criteria systems. Experiences of countries, territories and international organizations in the world show us the principles, system of criteria, processes as well as methods of selection, forms of honoring science, technology and innovation products, which is quite strict, public, transparent and has its own standards, specific to each industry and field. Through the experience of other countries and international organizations, Vietnam can refer to develop the process, selection criteria, evaluation, as well as the form of honor the science, technology and innovation products. This is also a communication channel for science, technology and innovation products to people in Vietnam as well as in the world.